Taaruf from the Perspective of Social Penetration Theory (A Study of Marital Relationship Development Among Alumni Couples of TMI Al-Amien Prenduan) - Azka Diana; Ahmad Zulfikar Ali (al-Afkar, Journal For Islamic Studies, 2026)
Advancements in communication technology have influenced interpersonal relationship patterns, leading to the normalization of dating culture among modern teenagers. Islam offers an alternative approach to relationships that aligns better with religious values specifically, the taaruf process as a pathway to marriage. However, taaruf entails limitations, notably the brief duration of the acquaintance period prior to marriage. Consequently, the process of getting to know one another does not cease before the wedding but continues into the marriage itself. This study aims to examine the evolution of interpersonal communication between couples who married through taaruf, applying the framework of Altman and Taylor’s Social Penetration Theory. Employing a descriptive qualitative approach, the study focuses on five married couples all alumni of the TMI Al-Amien Prenduan Islamic boarding school who entered into marriage via taaruf. Data collection was conducted at the TMI Al-Amien Prenduan Islamic boarding school using in-depth interviews and documentation. The analysis reveals that interpersonal communication between these couples evolved gradually after marriage, mirroring the stages outlined in Social Penetration Theory. Furthermore, a shared background specifically, having attended the same Islamic boarding school served as a crucial factor in accelerating the development of their communication, as it fostered a shared mindset and common experiences. Thus, the communication limitations inherent in the taaruf phase did not hinder the establishment of a harmonious interpersonal relationship after marriage.